Moving on from adversity: an understanding of resilience in rural Thai older people. (4th March 2019) - Pathike, Wilaiwan; O'Brien, Anthony Paul; Hunter, Sharyn
ABSTRACT: Objective: This study explored the concept of resilience in rural Thai older people. Method: The study was exploratory and descriptive in design. Ethnographic fieldwork was undertaken in four rural Thai communities. Non-participant observation (340 h) and 35 semi-structured interviews with older people enabled the collection of qualitative data. Nvivo 10 was used to collate and organise the qualitative data. Data analysis was conducted thematically. Results: One major core theme and five qualitative sub-themes emerged from the data related to the theoretical construct of rural Thai elders' resilience. The subthemes of the core theme 'moving on' include: (1) keep doing a job and earning a living; (2) having Jai-Yai to fight for life; (3) accepting a situation (Plong and Taam-Jai); (4) expressing difficulty; and (5) connecting with people, beliefs and customs. Conclusion: The concept of 'moving on' provides a subcultural viewpoint of older rural Thai people in the face of adversity in their everyday lives. Previous conceptions of resilience and older people focus on it being bouncing back from adversity. Bouncing back implies a setback, whereas 'moving on' found in this study is the process of continuous movement forward and getting on with one's life despite difficulties.